Acidification indices and organic carbon characteristics of acidic soil with different straw incorporation rates (Bangladesh Journal of Botany, 2025)
This study analyzed the acidification indices and organic carbon differences of acidic tobacco-growing soils with different straw incorporation rates. The results showed that the Tengchong acidic tobacco-growing soil had low potential acidity and high base saturation. The long-term straw incorporation increased the organic matter year by year, but the soil pH in the tobacco growing season showed a decreasing trend. The ratio of humic acid to extractable humus (PQ), HA/FA value, E4 value, the rA value at 1630/cm in the infrared emission peak band, and the relative area after integration were significantly higher than those of the soils from Changning Jifei Town and Yongan Xiyang Town. The E4/E6 value, △logK value, and A2920/A1630 value of the soil collected from Tengchong were lower than those of soils from the other two areas. Thus, the soil from Tengchong had a high relative HA content in its humus composition and a complex organic carbon structure.Bangladesh J. Bot. 54(3): 631-644, 2025 (September) Special